Zodiak Sebagai Ekspresi Dalam Penciptaan Karya Seni Lukis - Kristina, Renata Ayu; Setem, I Wayan; Purnami Utami, Ni Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
This thesis raises the theme of "Zodiac as Expression in the Creation of Paintings" from an observation of various types of behavior, characters, and characteristics of the zodiac. This gives rise to the urge to bring the expressions of the zodiac cancer, pisces, and scorpio into abstract style paintings. In the embodiment of the work, the style used is a combination of naturalism and abstractionism, which are the characteristics of Mr. Made Budhiana's painting as a partner in the independent study program of the Merdeka Learning Campus Merdeka. With the aim and benefit of providing an understanding of the zodiacal character of the water element, the author expresses ideas that are processed using qualitative methods, equipped with interview guidelines, reduction and presentation of data that can be used as ideas in creating a painting. Ideas or ideas cannot be separated from observations and interactions with surrounding conditions and personal experiences so that the author can express the feelings of the zodiac character with the water element in the painting. The idea obtained also comes from astrological records that have been studied since time immemorial, namely the Ancient Greek tradition that is spread on social media. So it can be concluded that this painting with the theme of the water element zodiac can be used as a reference to understand a person's character, especially the Cancer, Pisces, and Scorpio zodiacs in everyday life